Urban Redevelopment Program and Demand Externality - Daiji Kawaguchi; Keisuke Kawata; Chigusa Okamoto (Institute of Labor Economics (IZA), 2024)
Demand externality generated by the agglomeration of commercial activities is a potential source of city formation. We study the impact of a large-scale urban redevelopment program involving the construction of a shopping complex at the center of Tokyo. The redevelopment program increased the land price and commercial building use in its neighborhood. It also increased the total sales of neighborhood firms but not their profits. We argue that the redevelopment program generated substantial demand externality but the benefit fell on the landlord.
Keywords: R12; R14; R52; 330; demand externality; shopping externality; urban redevelopment program